Mathematics for the Curious - Higgins P. Peter (New York, Oxford University Press, 1998)
When do the hands of a clock coincide? How likely is it that two children in the same class will share a birthday? Should you play Roulette or the Lottery? How do we calculate the volume of a doughnut? Why does the android Data in Star Trek lose at poker? What-is Fibonacci's Rabbit Problem? Many things in the world have a mathematical side to them, as revealed by the puzzles and questions In this book. It is written for anyone who is curious about mathematics and would like a simple and entertaining account of what it can do. Peter Higgins provides clear explanations of the more mysterious features of childhood mathematics as well as novelties and connections to prove that mathematics can be enjoyable and full of surprises.